Studies of Raspy Crickets: The Status of the Wingless American gryllacridines (Orthoptera: Gryllacrididae) - Cadena-Castañeda, Oscar J.; Quintana-Arias, Ronald Fernando (Zootaxa, 2024)
In this contribution based on the American wingless gryllacridines, the two genera described for the New World Camptonotus and Neoeremus are defined and differentiated, resulting in three additional genera: Neortus stat. resurr., Fiancogryllacris n. gen. and Camposgryllacris n. gen. The species of these genera were described at the end of the 19th century and the beginning of the 20th century, and in most taxa, there are no records since their description, so the iNaturalist platform provided additional distributional data for some species. Taxonomic keys are provided for the identification of the genera and species studied. Finally, the evolutionary interpretation of the appearance and disappearance of wings in leaf-rolling crickets are discussed.